Effectiveness of clove oil anesthesia on the performance and survival of Batak fish (Tor soro) fry during transportation - Rumondang, Anne; Effendi, Irzal; Supriyono, Eddy (Acta Aquatica: Aquatic Sciences Journal, 2025)
This study aimed to evaluate the effectiveness of clove oil as a natural anesthetic for Batak fish juveniles during transportation. The experiment was conducted using a Completely Randomized Design (CRD) with four treatment levels of clove oil: P0 (control/0 ml/l), P1 (0.01 ml/l), P2 (0.02 ml/l), and P3 (0.03 ml/l), each with three replicates. Observed parameters included physiological responses (induction time, recovery time, and behavior), survival rate, and water quality before and after transportation. The results indicated that clove oil significantly affected the physiological responses of Batak fish juveniles, although it did not significantly influence survival rates, which remained above 90% for all treatments. The optimal concentration was 0.01 ml/L, with an average induction time of 64 minutes and recovery time of 1.15 minutes. During transportation, water temperature increased from 27.48 °C to 29.53 °C, pH decreased from 7.22 to 7.17, and dissolved oxygen (DO) decreased from 5.38 mg/l to 5.32 mg/l. These changes remained within the tolerance range of Batak fish juveniles, thus not affecting survival. The findings demonstrate that clove oil effectively reduces physiological stress and maintains water quality, suggesting that it can be recommended as a safe, efficient, and environmentally friendly natural anesthetic for transporting Batak fish juveniles. Keywords: Anesthesia; Clove Oil; Survival Rate; Tor soro; Transportation